Unnecessary Removal of Central Venous Catheters in Cancer Patients with Bloodstream Infections: Impact on Symptom Burden. (4th October 2017) - Chaftari, Anne-Marie; Raad, Sammy; Hachem, Ray Y; Shah, Pankil; Jiang, Ying; Natividad, Elizabeth; Cleeland, Charles; Rosenblatt, Joel; Raad, Issam
Abstract: Background: Current IDSA guidelines mandate removal and re-insertion of Central Venous Catheters (CVCs) in the setting of central line associated bloodstream infections (CLABSI) caused by virulent pathogens. However, CVC may be retained in the setting of non-CLABSI. There has been little if any quantitative assessment of the symptom burden associated with CVC removal and insertion. Methods: Between 2013 and 2014, we evaluated the rate of CVC removal in 283 cancer patients who presented at our institution with a bloodstream infection (BSI) in the presence of a CVC whereby the positive blood cultures were drawn from the CVC and peripheral vein. In 2015, we collected symptom burden related to CVC removal and insertion procedures in 60 consecutive cancer patients using the MD Anderson Symptom Inventory. Results: The rate of CVC removal in patients with BSI and other non-CVC source was 57% which was identical to that in patients with CLABSI. ( P = 0.94). In the 60 patients evaluated for symptom burden, symptoms (such as pain, pressure, distress) were present in up to 57% to 67% of patients undergoing CVC insertion and removal respectively. In 32% of patients, moderate to severe symptoms were reported with a symptom burden level of 4/10 or more. Conclusion: CVC removal occurred unnecessarily in 57% of non-CLABSI patients which was equivalent to that in patients with CLABSI. Catheter removal and insertion produced moderate to severe symptom burden in cancer patients. Physician education need to be reinforced and safe interventions to salvage the vascular access should be explored. Disclosures: J. Rosenblatt, Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Rosenblatt is a and Shareholder, Licensing agreement or royalty; UT MD Anderson Cancer Center: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Rosenblatt is a s and Scientific Advisor, Licensing agreement or royalty; I. Raad, Merck: Grant Investigator, Research grant; Allergan: Grant Investigator, Research grant; Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Raad is a s and Shareholder, Licensing agreement or royalty.